Big data, dementia prediction and knowledge organization - D. Grant Campbell (Informatio, 2025)
This paper uses principles of knowledge organization to explore the application of big data algorithms to the task of predicting dementia diagnoses. Using the principles of domain analysis, the paper argues that domains, as distinct from academic disciplines, provide a more flexible, and therefore more useful way of understanding the different discourse communities involved in dementia prediction. Using the distinction between the epistemological, applied and sociocultural dimensions of knowledge organization, the paper extracts a series of important questions and ambiguities that face both technology-related and dementia-related domains in the area of dementia prediction.